Wpływ wczesnej interwencji neurologopedycznej w terapii dziecka urodzonego przedwcześnie – studium przypadku - Zawichrowska , Marta (Studia Edukacyjne, 2023)
The shows the impact of early neurological intervention in the treatment of a premature baby from the perspective of feeding difficulties. I will discuss the ambiguous definitions of early intervention and diagnosis from the perspective of the interdisciplinarity of speech therapy. I will also present the diagnostic and therapeutic steps in the therapeutic feeding work of an extreme preterm infant at risk of disability, taking into account the child’s capabilities and limitations.